Influence of Cellulose on the Mechanical and Thermal Stability of ABS Plastic Composites. (19th May 2016) - Crews, K.; Huntley, C.; Cooley, D.; Phillips, B.; Curry, M.
Abstract : Microcrystalline cellulose was explored as possible biodegradable fillers in the fabrication of ABS plastic composites. TGA indicates that upon inclusion of cellulose microcrystals the thermal stability of the ABS plastics was improved significantly when compared to the neat ABS plastic counterparts. Furthermore, inclusion of extracted cellulose from plant biomass showed a higher thermal stability with maximum decomposition temperatures around 131.95°C and 124.19°C for cellulose from cotton and Hibiscus sabdariffa, respectively, when compared to that of the purchased cellulose. In addition, TMA revealed that the average CTE value for the neat ABS and 1 : 1 ratio of cellulose to ABS fabricated in this study was significantly lower than the reported CTE (ca. 73.8 μ m/m°C).